FTIR DERIVATIVE SPECTRA ANALYSIS OF BEEF AND PORK PROTEIN - Adang - Firmansyah; O - Suprijana; Yulia - Riesmawati (Sekolah Tinggi Farmasi Indonesia, 2015)
AbstractAccording to recent investigations on beef adulteration, there are many cases found that beef mixed with pork . PCR (Polymerase Chain Reaction) as the method of choice for such analysis are considered to be relatively expensive and less practical. It would be necessary to develop a simple alternative methode which could differentiate beef and pork. The purpose of this research was to analyze beef and pork using FTIR spectrophotometry. Main FTIR spectrum and first derivative spectrum were used for analysing beef and pork of fresh samples (unprepared), crushed sample and denaturated by heating. The result indicate that FTIR spectrum was relatively repeatable for all prepared samples. Infrared absorption bands of beef is more complex than pork which almost all of the infrared absorption bands found in the spectrum of beef, except for the presence of absorption at wave numbers 1068-1017 cm-1 and clarified on first derivative spectrum. This unique peak considered could be used as reference peak for analysing pork protein or adulteration of beef with pork. Keywords : beef, pork, FTIR spectrophotometry, first derivative spectra